114k views
3 votes
How many solutions does 4x + 2(x – 3) = 4x + 2x – 11 have?

User Caverac
by
5.4k points

2 Answers

3 votes

Answer:

0 solution

Explanation:

4x + 2(x – 3) = 4x + 2x – 11

Solve the parentheses:

4x + 2x - 5 = 4x + 2x - 11

Subtract 2x from both sides:

4x - 5 = 4x - 11

From what you can already see that those two expressions does not equal to each other. Let’s continue solving to confirm:

(Subtract 4x on both sides)

-5 = -11

There are 0 solutions

~

User Arshan
by
4.3k points
3 votes

Answer:

4x + 2(x – 3) = 4x + 2x – 11

4x + 2x - 6 = 4x + 2x - 11

6x - 6 = 6x - 11

-6 = -11

There is no solution because -6 does NOT equal -11

User Banning
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.